Critical Points of Halal Antioxidants from the Perspective of the Qur’an, Science, and Health - Nur Arifani, Erlina; Mahfudz, Muhammad Syarqim (Kaunia: Integration and Interconnection Islam and Science Journal, 2024)
Oxidation reactions in oil or fat cause changes in the fat structure and produce a rancid odor. So to prevent this rancidity reaction, antioxidants are needed. Oil or fat is a triglyceride consisting of one glycerol and three fatty acid groups. These fatty acids are easily changed by reaction with oxygen, resulting in unwanted rancidity. Antioxidants that are often used in the oil and oily food industry vary. Some come from synthetic materials, and some come from natural materials. Each has its own advantages and disadvantages, both in terms of halal and health aspects (Tayyib). Halal is a requirement in food products in Indonesia and is regulated in laws and regulations to protect Muslims who are required to eat halal food. Food ingredients must also be guaranteed halal so that the final product can be labeled halal. If we can choose, of course we prefer natural antioxidants that come from halal ingredients and are coated with halal ingredients as well. Thus, the Halal and Tayyib requirements for our bodies will be met. Bamboo Leaf Extract (Bambusa sp) is one of the Natural Antioxidants that comes from Nature. In this study, the Antioxidant in Bamboo Leaves (Bambusa sp) was obtained at 45.22 μg / mL. The critical point of halal Antioxidants can be reviewed based on the purpose of use, the source of the raw materials, and the processing method.